Peripherally inserted central catheters versus implanted port catheters in patients with breast cancer: a post hoc analysis of the PICCPORT randomised controlled trial - Anton Utas; Stefanie Seifert; Knut Taxbro (BJA Open)
Background: Breast cancer is the most prevalent malignancy affecting women. However, the optimal strategy for patients requiring long-term central venous catheters in breast cancer treatment remains uncertain. Previous investigations involving a mixed cancer population have shown a higher frequency of adverse events among patients receiving peripherally implanted central catheters (PICCs) compared with totally implanted central catheters (PORTs). Our study aimed to compare catheter-related adverse events in breast cancer patients. Methods: We conducted a post hoc analysis of a previously published multicentre RCT known as PICCPORT. Data pertaining to baseline characteristics, insertion specifics, complication rates, and patient satisfaction were collected for breast cancer patients who required long-term central venous catheters for cancer treatment. The primary endpoint was a composite variable encompassing thrombotic, occlusive, infectious, or mechanical complications, while patient satisfaction served as a secondary endpoint. Results: Our analysis included 80 patients receiving PORT and 78 patients receiving PICC. There was no statistically significant difference in the incidence of complications between the PICC and PORT groups. Interestingly, PICC insertion was less painful than PORT insertion, although both groups reported low levels of pain. Conclusions: While acknowledging the limitations of an underpowered post hoc subgroup analysis, our findings suggest that the well-established superiority of PORTs in terms of adverse events among cancer patients might not be as substantial for breast cancer patients in particular. Ultimately, the optimal strategy for selecting long-term access devices in breast cancer patients remains to be determined. Clinical trial registration: NCT01971021.